Comparative Study of the Reactivity of Zirconium(IV)‐Substituted Polyoxometalates towards the Hydrolysis of Oligopeptides. Issue 13 (8th April 2015) - Ly, Hong Giang T.; Absillis, Gregory; Parac‐Vogt, Tatjana N.
Abstract: The hydrolytic activity of the Zr IV ‐substituted Keggin‐type (Et2 NH2 )8 [α‐PW11 O39 Zr‐(μ‐OH)(H2 O)2 ]· 7H2 O (1 ), Lindqvist‐type (Me4 N)2 [W5 O18 Zr(H2 O)3 ] (2 ), and Wells–Dawson‐type Na14 [Zr4 (P2 W16 O59 )2 (μ3 ‐O)2 (OH)2 (H2 O)4 ]· 57H2 O (3 ) polyoxometalates (POMs) towards the peptide bonds in the oligopeptides triglycine, tetraglycine, glycylglycylhistidine, and glycylserylphenylalanine was investigated by kinetic methods and multinuclear NMR spectroscopy. 31 P NMR and UV/Vis spectroscopy showed that1 –3 were stable under the conditions used to study peptide bond hydrolysis. The reactivity of1 –3 towards oligopeptides was compared on the basis of the amount of free glycine produced at a certain time increment. In the presence of1 –3, rate constants in the range 6.25 × 10 –7 to 10.14 × 10 –7 s –1 were obtained, whereas no hydrolysis was observed after one month in the absence of these POMs. The results showed that the Keggin‐type complex1 was the most active towards peptide bond hydrolysis in tri‐ and tetrapeptides. 1 H and 13 C NMR spectroscopy showed that triglycine, tetraglycine, and glycylserylphenylalanine interact with1 and2 preferentially through the amine nitrogen atom and the N‐terminal amide oxygen atom to activate the peptide bond towards hydrolysis. The coordination of glycylglycylhistidine resulted in multiple complexes with1 –3 as a result of additional imidazole coordination to the Zr IV centers. Abstract : The hydrolytic activity of Zr IV ‐substituted Lindqvist‐, Keggin‐, and Wells–Dawson‐type polyoxometalates towards the peptide bonds in tri‐ and tetrapeptides is investigated by kinetic methods and multinuclear NMR spectroscopy. The peptides are hydrolyzed completely in nearly neutral and neutral pH media. The Keggin complex is the most active towards peptide bond hydrolysis in the studied peptides.